The Relationship Between Internet Use And Adolescent Sexual Behavior - Muthahharah; Eka Hadrayani; Huriati; Yunita Vebrianti Amanda (Window of Health : Jurnal Kesehatan, 2026)
The increasing use of the internet among adolescents may influence risky sexual behavior. This study aimed to determine the relationship between internet use and sexual behavior among 11th-grade students at SMA Negeri 1 Gowa using a quantitative cross-sectional design. A total of 189 respondents were selected through simple random sampling. Data were collected using structured questionnaires and analyzed using the Chi-square test. The results showed that 57.7% (109 students) were heavy internet users and 59.3% (112 students) engaged in risky sexual behavior. Among heavy internet users, 71.6% demonstrated risky sexual behavior, compared to 42.5% among light users, indicating a higher likelihood of risky behavior in adolescents with greater internet use. Statistical analysis revealed a significant association between internet use and sexual behavior (p < 0.05), demonstrating a meaningful relationship between the variables. In conclusion, heavy internet use is associated with an increased risk of unsafe sexual behavior among adolescents. These findings highlight the importance of adolescent health programs that strengthen parental supervision, improve digital literacy, and promote responsible internet use to prevent risky sexual behavior.